Nepal-India Political Relations: A Comprehensive Analysis of Historical Dynamics, Contemporary Challenges, and Future Prospects - Mahar, N. S. (Pragya Darshan प्रज्ञा दर्शन, 2024)
This research provides a comprehensive analysis of the historical dynamics, contemporary challenges, and future prospects in Nepal-India political relations. The diplomatic ties between the two nations, rooted in shared history, cultural affinities, and geographical proximity, have witnessed both cooperation and discord over the centuries. While historical documents highlight periods of mutual respect, the study delves into the complexities of the Treaty of Peace and Friendship in 1950, solidifying diplomatic bonds. However, recent years have seen a shift in this narrative, marked by territorial disputes, economic imbalances, and evolving geopolitical dynamics. Contemporary challenges include territorial disputes leading to diplomatic intricacies and economic imbalances raising questions about the equitable nature of the bilateral relationship. The research adopts a mixed-methods approach, combining historical analysis, policy examination, and stakeholder perspectives to offer timely and relevant insights. Key informant interviews with political leaders, diplomats, and professionals provide a diverse understanding of the multifaceted issues at hand. The study identifies territorial disputes and unequal diplomatic treaties as major challenges, contributing to tensions in Nepal-India relations. It emphasizes the need for a peaceful discourse to resolve border encroachments and calls for a revision of existing treaties in light of changing regional and international circumstances. Additionally, socio cultural affinities between the two nations are explored, with strategies proposed for bridging gaps and fostering a sense of shared identity. The research concludes with strategies for future cooperation, advocating for a balanced diplomatic relationship that considers the changing global landscape. The equidistance principle is discussed, urging both nations to adapt their mindsets and refrain from micromanaging each other's domestic politics. The study underscores the importance of recognizing the historical ties between Nepal and India, emphasizing the potential for multifaceted alliances in the future.